2002
DOI: 10.1038/ng988
|View full text |Cite
|
Sign up to set email alerts
|

Regional loss of imprinting and growth deficiency in mice with a targeted deletion of KvDMR1

Abstract: Genomic imprinting is an epigenetic modification that results in expression from only one of the two parental copies of a gene. Differences in methylation between the two parental chromosomes are often observed at or near imprinted genes. Beckwith-Wiedemann syndrome (BWS), which predisposes to cancer and excessive growth, results from a disruption of imprinted gene expression in chromosome band 11p15.5. One third of individuals with BWS lose maternal-specific methylation at KvDMR1, a putative imprinting contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
409
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(427 citation statements)
references
References 29 publications
16
409
0
2
Order By: Relevance
“…These data indicate that Eed represents an additional mechanism of epigenetic regulation that is required to maintain parent-oforigin expression at specific loci in this cluster. In Eed -/-embryos, Cdkn1c and Ascl2 had LOI but Slc22a1l, Tssc3 and Kcnq1 were properly imprinted, whereas all imprinted genes in the cluster were affected in the KvDMR1/Kcnq1ot1 deletion 19 . Gene-specific LOI was also observed in the cluster of imprinted genes on chromosome 12 (ref.…”
Section: These Data Identify Eed As a Member Of A New Class Of Trans-mentioning
confidence: 93%
See 1 more Smart Citation
“…These data indicate that Eed represents an additional mechanism of epigenetic regulation that is required to maintain parent-oforigin expression at specific loci in this cluster. In Eed -/-embryos, Cdkn1c and Ascl2 had LOI but Slc22a1l, Tssc3 and Kcnq1 were properly imprinted, whereas all imprinted genes in the cluster were affected in the KvDMR1/Kcnq1ot1 deletion 19 . Gene-specific LOI was also observed in the cluster of imprinted genes on chromosome 12 (ref.…”
Section: These Data Identify Eed As a Member Of A New Class Of Trans-mentioning
confidence: 93%
“…5a), as paternal inheritance of a deletion of KvDMR1 results in LOI at these imprinted loci 19 . The observed LOI at these loci may be due to removal of the CpG island at the ICR or to disruption of the Kcnq1ot1 antisense transcript.…”
Section: These Data Identify Eed As a Member Of A New Class Of Trans-mentioning
confidence: 99%
“…This causes growth retardation, which supports the hypothesis that abnormal silencing at CDKN1C and other genes along the domain negatively affects growth. (17) Aberrant imprinting maintenance and growth disorders ICRs carry epigenetic marks that are established in the germ cells and, after fertilisation, are maintained throughout development. Proper establishment, and especially the subsequent somatic maintenance of these marks, is crucial, since their deregulation may lead to complex diseases in humans, and is frequently also observed in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the mouse, deletion of the H19 ICR does not affect the KCNQ1 domain and, conversely, targeting of the KvDMR1 does not alter imprinting at the IGF2-H19 domain. (17,34,35) An emerging question is whether, as opposed to what happens in BWS, increased expression of CDKN1C could be causally involved in SRS. In the novel SRS studies, this was explored by analysis of the KvDMR1, but no methylation changes were detected in the patients analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Kcnq1ot1, a nuclear-retained lncRNA with the length of 91.5 kb, is transcribed by RNAPII from the intron 10 of Kcnq1 gene in an antisense orientation to Kcnq1 [38]. The production of Kcnq1ot1 RNA was first found to be associated with the lineage-specific silencing of dozens of genes within the Kcnq1 locus [38,39]. Recent studies further indicated that the silencing effects are achieved by the interactions of Kcnq1ot1 with chromatin and with the H3K9-and H3K27-specific histone methyltransferases G9a and the polycomb repressive complex 2 (PRC2) [40].…”
Section: Epigenetic Regulationmentioning
confidence: 99%